Prevalence of High-risk Pregnancy and Utilization of Conditional Cash Transfer Schemes in One of the Rural Areas of Eastern India - Varsha Rajan; Bimal Kumar Sahoo; Priyamadhaba Behera; Binod Kumar Patro; Manish Taywade (Current Medical Issues)
Background: Early identification of high-risk pregnancies is essential in reducing maternal and infant mortality. The Mamata scheme, a conditional cash transfer program, aims to support pregnant women and lactating mothers by improving access to essential care and nutrition. This study aimed to assess the prevalence of high-risk pregnancies and utilization of Mamata scheme in rural Odisha. Materials and Methods: A cross-sectional study was conducted in the rural field practice area of AIIMS, Bhubaneswar, from June 1, 2021, to August 30, 2021. Women of reproductive age with amenorrhea for over 1 month were included through universal sampling. After confirming pregnancy, a structured questionnaire was used to assess registration status, eligibility for Mamata scheme, and high-risk pregnancy conditions. Results: Out of 143 participants in the study, the prevalence of high-risk pregnancies was 25.17% (95% confidence interval [CI]: 18.06–32.26). Among them, 70% were identified due to past pregnancy history, 22% based on current pregnancy history, and 8% had high-risk factors from both past and current pregnancy histories. Among identified high-risk pregnancies, the most common risk factor was those who had a previous cesarean section or any uterine surgery (38.88%). For Mamata scheme, among participants, 64.34% (95% CI: 55.90–72.16) met the eligibility criteria. The enrolled were 96.50% (95% CI: 92.03–98.85) in the scheme, which reflects the widespread access to conditional cash transfers. Conclusions: The study highlights a significant prevalence of high-risk pregnancies in rural areas, alongside high enrolment in Mamata scheme. Public health measures are required to empower community health workers regarding early identification of high-risk pregnancies and linkage with appropriate care.